Evaluasi Profil Sensori Permen Chocolate Fudge dengan Penggunaan Susu Nabati Metode RATA (Rate-All-That-Apply): The Evaluation of Sensory Profile of Chocolate Fudge Candy Using the Vegetable Milk Method (Rate-All-That-Apply) - Pramadita Amila Shaliha; Sri Rejeki Retna Pertiwi; Aji Jumiono (Universitas Djuanda, 2025)
Plant-based chocolate fudge has become a popular food innovation, especially among consumers with lactose intolerance and those following vegetarian or vegan diets. Plant-based milks such as almond, soy, and oat not only serve as alternatives to dairy milk but are also known for their health benefits, including unsaturated fats and bioactive compounds that support heart health. This study aimed to investigate the sensory characteristics of chocolate fudge formulated with three types of plant-based milk using the Rate-All-That-Apply (RATA) method. The evaluation was conducted through Focus Group Discussion (FGD) and consumer testing involving 60 panelists. The assessed attributes included color, aroma, texture, taste, and overall flavor. Statistical analysis using Kruskal-Wallis and Duun’s Test identified five significantly different attributes: dark brown color, glossy appearance, fudgy and fatty textures, and milky flavor. Principal Component Analysis (PCA) and Preference Mapping revealed that each type of plant-based milk contributed unique sensory profiles. Fudge made with oat milk exhibited a darker color and a more fudgy and fatty texture, while almond milk produced a stronger chocolate aroma and creamier flavor that were more preferred. Fudge made with almond and soy milk received higher consumer preference scores than oat-based fudge. These findings demonstrate that the choice of plant-based milk significantly affects the sensory profile and consumer preferences, supporting the development of healthier chocolate products.